XPS Analysis of Surface Texture of Coking Coal in Fenxi County - Ge, Tao; Zhang, Mingxu; Cai, Chuanchuan (Asian Journal of Chemistry, 2014)
With the adoption of XPS method, this paper is aimed at the research into the surface texture of the sample coal of Fenxi county, with the outcome as follows. There is a low content of nitrogen and carbonyl and carboxyl in the coal,with carbon mainly existing in the form of C-C. Most oxygen in the coal exists in the form of phenolic hydroxyl and ether oxygen.In organic sulphur constitutes a small percentage in the coal, with organic sulphur,in the three major forms of (sub) sulfone, thiophene and thiol (ether).